2013
DOI: 10.5552/drind.2013.1301
|View full text |Cite
|
Sign up to set email alerts
|

Innovation and Innovativeness in Medium-Low Tech/Low-Tech Industries – Wood Industry

Abstract: • Krajnji cilj inovacije jest poboljšanje poslovanja, a inovacijske aktivnosti u suvremenim uvjetima

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…For instance, Pirc and Vlosky [10] showed that applying innovation is becoming more and more important in Croatian furniture companies. Barčić and Motik [2] revealed that, along with small traditional companies, innovative companies in the Croatian furniture industry exist, but due to excessive market opportunities and possibilities, managers, directors, and executive staff still do not recognize which way will take them to one step ahead of the competition.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Pirc and Vlosky [10] showed that applying innovation is becoming more and more important in Croatian furniture companies. Barčić and Motik [2] revealed that, along with small traditional companies, innovative companies in the Croatian furniture industry exist, but due to excessive market opportunities and possibilities, managers, directors, and executive staff still do not recognize which way will take them to one step ahead of the competition.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Due to the COVID-19 pandemic, the concentration of suppliers or customers along the chain may make some firms more vulnerable to shocks from the crisis. Additionally, for industries with high concentrations of exports or imports, fewer possibilities for suppliers or buyers to be replaced exist in the event of a break in the chain [2].…”
Section: Introductionmentioning
confidence: 99%
“…For example, market share of more innovative companies tends to increase in volume, in contrast to the underperforming companies whose failure forces them to search for innovation opportunities. Consequently, the companies that base their progress on innovativeness stand a better chance of having higher export values (Pirc-Barčić and Motik, 2013).…”
Section: Introduction 1 Uvodmentioning
confidence: 99%